Народнопісенні діалекти Сумщини (досвід мелоареалогічного дослідження) - Гончаренко, О. (Народна творчість та етнографія, 2008)
In the traditional song culture in the north-east of Ukraine (modern Sumska region) many contrast local styles were formed. The author of the article created maps of calendar and ritual genres and wedding rhytmical types, she described musical dialects, explicated areas of their localization, defined lines of dissociation or diffusive zones of styles crossing.